Using eye temperature and heart rate for stress assessment in young horses competing in jumping competitions and its possible influence on sport performance. (26th September 2013) - Bartolomé, E.; Sánchez, M. J.; Molina, A.; Schaefer, A. L.; Cervantes, I.; Valera, M.
Abstract : The aims of this study were, first, to evaluate eye temperature (ET) with infrared thermography and heart rate (HR) to measure stress in horses during show jumping competitions and their relationship with competition results, and second, to evaluate the influence of different extrinsic and intrinsic factors of the horse on the stress measurements analysed. One hundred and seventy-three Spanish Sport Horses were analysed for ET and HR, and these measurements were taken 3 h before the competition, just after and 3 h after it. Two interval measurements were also assessed for each parameter. Positive significant correlations were found between ET and HR, measured before ( r =0.23), just after competition ( r =0.28) and for the later interval ( r =0.26), whereas negative correlations with competition results were found only for ET when measured just after competing ( r =−0.25). Two intrinsic factors (genetic line and age) and no extrinsic factors showed significant differences for ET, whereas one intrinsic factor (age) and two extrinsic factors (journey duration and number of training hours) showed significant differences for HR. The marginal means showed significantly higher ET values for the Anglo-Arab genetic line and for 5-year-old animals. HR values were significantly higher for 4-year-old animals, for horses which had travelled 4 to 6 h and for horses that had 3 to 6 h of daily training. This study suggests that, although ET and HR seemed to share a similar physiological basis, the factors that most influenced each parameter were different. Finally, ET seems to be a suitable tool for assessing stress during show jumping competitions in horses.